2009
DOI: 10.3141/2120-02
|View full text |Cite
|
Sign up to set email alerts
|

Methodology to Predict Driver Vision Impairment Situations Caused by Sun Glare

Abstract: This paper presents a methodology to determine the days and times of the year when sun glare may impair drivers’ vision on a particular road section, depending on the geographic location, the geometric design of the road, and the physical characteristics of the environment. The methodology is based on applying cylindrical charts to represent the entire set of variables involved in the problem. The results may be used to study in detail the problem at critical sections of existing or newly designed roads such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Furthermore, we classified crashes as being related to glare when the angular distance between the driver’s line of sight and the sun was between 0° and 45°, a threshold based on research in Japan 13. Further research adopting more stringent thresholds of 10°, 20° or 30° degrees or analysing the changes in this effect for motorists of different ages may attempt to compare their results with ours, as indicated by Jurado-Piña and Pardillo Mayora 9…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Furthermore, we classified crashes as being related to glare when the angular distance between the driver’s line of sight and the sun was between 0° and 45°, a threshold based on research in Japan 13. Further research adopting more stringent thresholds of 10°, 20° or 30° degrees or analysing the changes in this effect for motorists of different ages may attempt to compare their results with ours, as indicated by Jurado-Piña and Pardillo Mayora 9…”
Section: Discussionmentioning
confidence: 68%
“…Churchill et al 8 employed a geometric model to examine whether sun glare affects the speeds of drivers on roadways and concluded that changes in speed as a result of sun glare affected highway congestion. Jurado-Piña and Pardillo Mayora,9 in an investigation of the maximum tolerable sun glare determined that glare occurs when at specific angular distances between a driver’s line of sight and the sun; these angular distances are 19° for a 40-year-old driver and 25° for a 60-year-old driver. Anue10 suggested that sun glare typically does not occur at angular distances greater than 25°.…”
Section: Introductionmentioning
confidence: 99%
“…An examination has been directed in Japan to discover the commitment of sun glare in RTAs [119,120]. Depicted that the frequency of RTAs, as a rule, goes higher when sun presentation was before engine vehicles than the person on foot mishaps [121]. They likewise saw that RTAs happened with more noteworthy recurrence when the vehicle has a direct front introduction towards the sun.…”
Section: Impact Of the Low Sun (Glare) On Road Traffic Accidentsmentioning
confidence: 99%
“…The population that is more likely to suffer vision impairments are older drivers, 60 years of age, or older. Numerous studies suggest that eyesight deteriorates with age and it also becomes more sensitive to automatic changes in the environment, resulting in a sight adaptation lag (Jurado-Piña and Pardillo-Mayora, 2009;Auffray et al, 2008;Jurado-Piña, Pardillo-Mayora and Jiménez, 2010;Yeung, Wong and Xu, 2013). So does this make older drivers more susceptible to crashing at or near tunnels?…”
Section: Statement Of Purposementioning
confidence: 99%
“…Periods of sun glare have been associated with increased probability for crashes (Jurado-Piña and Pardillo-Mayora 2009). Traffic observations show that there is a reduction in traffic speed and an increase in vehicle headways during times of high glare (Jurado-Piña and Pardillo-Mayora 2009).…”
Section: Sunlight Glarementioning
confidence: 99%